Actualization of Pancasila Student Profile at SDN 001 Peso in Outline Region - Sucahyo Mas’an Al Wahid; Kartini Kartini; Januar Alfredo (Journal on Education, 2024)
This study aims to pour basic understanding based on field data and actualization in having its own strategy to implement the Pancasila Student Profile through existing policies in schools, doing habituation such as mutual aid, praying before entering the classroom, and through extracurricular activities, as well as commemorating national and religious holidays. Supporting factors for the realization of the Pancasila Student Profile in elementary schools are parent and teacher cooperation, the environment, curriculum, and optimization in learning activities. As for the inhibiting factors, they are inadequate facilities and infrastructure, uneven technological advances, and the environment. The qualitative research method is to describe the findings that occur in the field using triangulation of student and teacher sources in the form of interviews in the form of structured interview sheet instruments related to positive activities in schools pancasila student profile content, time triangulation on teacher activities after teaching and parents of students after farming or other activities. The results of research on the actualization of pancasila student profiles related to routine, spontaneous, and exemplary habituation in schools to similar activities amounted to 45% in routine activities such as school ceremonies, class picket schedules and community service work. According to the profile of Pancasila students. Then in the spontaneous realm, 30% were found in the activity of throwing garbage in its place and playing with natural materials (sentokan, leppo), as well as on the example of saying greetings and visiting friends who were sick so that the activity was recorded at 23% according to the profile of pancasila students. In the learning content, 55% of the activities were fulfilled, consisting of praying before studying, being present on time, doing homework, and some students meet KKM. In the coaching content, namely the availability of school canteens, bag and shoe storage lockers, as well as report card assessments on neatness and personal hygiene so that a percentage of 38% is obtained according to the study of the theory and practice of pancasila students. It was concluded that some of the activities carried out, both measured and spontaneity, were in accordance with the strengthening of the profile of pancasila students in the aspects of faith and noble character, mutual cooperation and the value of independence.